Ethnobotanical Study of Medicinal Plants of Banjar and Java Tribes in Pandansari Village, South Kalimantan - Sutomo, Sutomo; Aprilianes, Alif Vera; Kartinah, Nani; Arnida, Arnida; Muslimawati, Khoirunnisa; Akbar, Nabila Hadiah (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
In Pandansari village, South Kalimantan, Indonesia, residents from Banjar and Javanese communities traditionally utilize medicinal plants as alternatives to conventional medicine. This study aimed to explore the demographics, plant use practices, and preliminary phytochemical analysis of these plants. Using a qualitative, phenomenological approach, semi-structured interviews and questionnaires were conducted with four purposively selected informants. The findings revealed 52 medicinal plant species. Leaves were the most commonly used plant part (40%), followed by boiling as the preferred processing method (54%) and drinking as the primary route of administration (58%). Two unidentified plants, asam sembelekan and daun malaysia, were frequently mentioned. Phytochemical screening detected flavonoids, saponins, phenols, and terpenoids in asam sembelekan, while daun malaysia contained alkaloids, flavonoids, saponins, and terpenoids. These findings provide a foundation for further research on the efficacy and safety of these traditional medicinal plants in this community.